Managerial incentive and the firms' propensity to invest in product and process innovation - Roberto Cellini; Luca Lambertini; Alessandro Sterlacchini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
We study the product and process innovation choice of firms in which a managerial incentive à la Vickers (1985) is present. Taking a two-stage game approach, we show that managerial firms are led to over-invest in process innovation, as compared to standard profit-maximising firms, while they under-invest in product innovation. The reason is that process innovation allows to decrease cost, and this is consistent with a convenient increase in the production level. On the opposite, product innovation allows increasing price, which is in contrast with the taste for output expansion embodied in the objective function of firms run by managers. Preliminary empirical evidence on Italian companies suggests that in fact the managerial nature of firm associates with significantly smaller efforts in product innovation while the effect on process innovation is positive but non-significant.
Keywords: 330